The Perspective of Al-Quran in Responding to Family Education in the Era of Industrial 4.0 - Jannah, Miftahul; Azami, Hadiana Trendi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The industrial revolution is a period in which technology is increasingly advanced accompanied by increasingly significant changes in the social, economic, and cultural fields. Communication technology is not only defined as a means of communication but can lead to the educational process. This brings great challenges for parents. Parents have to learn many things in order to direct their children to face the challenges in this era. So that children are able to take advantage of the development and progress of their time. The purpose of this study is to find out some verses of the Qur'an as a solution to the problems faced by families in the industrial era 4.0. This research was conducted by means of a literature study. The reference sources used are primary sources from a number of books and books as well as secondary sources from relevant journals. The result of this study is that the Qur'an explains the importance of cooperation between husband and wife to achieve family education, namely fostering the generation of qurratu a'yun, pious and pious generations. To face challenges in the industrial era 4.0, parents need to instill basic religious education to their children, namely Aqidah (faith), Knowledge of Halal and Haram, Moral Education, Worship Education, and skills education. This is an effort so that children can adapt to their times in accordance with applicable norms. The purpose of this study is to find out some verses of the Qur'an as a solution to the problems faced by families in the industrial era 4.0. This type of research is a literature study. The industrial revolution is a period in which technology is advancing, accompanied by increasingly significant changes in the social, economic, and cultural fields. This brings great challenges for parents. Parents have to learn many things in order to direct their children to face the challenges in this era. The results of this study are the family is the main basis in shaping the nation's generation and religion. Parents need to provide values as the role models for children. The pattern of this education is carried out through family education in order to create a generation that is able to respond to the challenges of the industrial era 4.0 in accordance with the teachings of Qur'an and Hadith. Hence, parents need to instill the basics of religious education to their children, namely Aqidah (faith), Fiqh, Moral, Worship, and skills education. This is an effort so that children can adapt to their times in accordance with applicable norms. Tujuan dari penelitian ini adalah untuk mengetahui beberapa ayat Al-Quran sebagai solusi dari permasalahan-permasalahan yang dihadapi keluarga di era industri 4.0. Jenis penelitian ini adalah studi literatur. Revolusi industri merupakan masa di mana teknologi semakin maju disertai dengan semakin signifikan perubahan pada bidang sosial, ekonomi, dan budaya. Hal ini membawa tantangan besar bagi orang tua. Orang tua harus mempelajari banyak hal agar dapat mengarahkan anaknya untuk menghadapi tantangan di era ini. Hasil dari penelitian ini adalah keluarga merupakan basis utama dalam membentuk generasi bangsa dan agama. Orangtua perlu memberikan nilai-nilai yang bisa menjadi teladan bagi anak-anak. Pola pendidikan tersebut dilakukan melalui pendidikan keluarga agar terwujud generasi yang mampu merespon tantangan era industri 4.0 yang sesuai dengan ajaran Al-Quran dan Hadis. Maka orangtua perlu menanamkan dasar pendidikan agama kepada anak yaitu Aqidah (faith), Fiqh, Akhlak, Ibadah, dan pendidikan keterampilan. Hal ini merupakan upaya agar anak mampu beradaptasi dengan zamannya sesuai dengan norma yang berlaku.